2018
DOI: 10.1029/2018jc013945
|View full text |Cite
|
Sign up to set email alerts
|

Interannual to Multidecadal Forcing of Mesoscale Eddy Kinetic Energy in the Subtropical Southern Indian Ocean

Abstract: A region of elevated mesoscale eddy activity spans the subtropical southern Indian Ocean (SSIO) between Madagascar and Australia. The interannual and decadal changes in eddy activity in the SSIO eddy band, as represented by the variability of eddy kinetic energy (EKE), have implications for the large‐scale circulation, mixed‐layer budgets, and biological activity. An analysis of nearly two and a half decades of sea level anomaly (SLA) data from merged satellite altimetry shows that, in the southeast Indian Oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Therefore, EKE is not an appropriate metric to characterize the KE of coherent mesoscale eddies. Generally, the signals of coherent mesoscale eddies could be obtained by applying spatial and/or temporal filters onto the SSHA or EKE field 23 25 . To properly do this, the typical spatial–temporal scales of mesoscale eddies (i.e., mean eddy size and lifetime) need to be identified in advance 25 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, EKE is not an appropriate metric to characterize the KE of coherent mesoscale eddies. Generally, the signals of coherent mesoscale eddies could be obtained by applying spatial and/or temporal filters onto the SSHA or EKE field 23 25 . To properly do this, the typical spatial–temporal scales of mesoscale eddies (i.e., mean eddy size and lifetime) need to be identified in advance 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the signals of coherent mesoscale eddies could be obtained by applying spatial and/or temporal filters onto the SSHA or EKE field 23 25 . To properly do this, the typical spatial–temporal scales of mesoscale eddies (i.e., mean eddy size and lifetime) need to be identified in advance 25 . Since these scales are subject to specific geographical domain 25 , it would be difficult to apply a universal scale in the analysis focusing on coherent mesoscale eddies in the basin-wide or global ocean.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the interannual scale, by examining long‐lived anticyclonic eddies, Fang and Morrow (2003) suggest that more warm eddies tend to be shed during anomalously warm conditions such as 1996 and 1999, with fewer in anomalously cold years such as 1997. By using long‐term satellite observations, it has been suggested that the EKE in the LC system is closely related to ENSO, with high values in La Niña years (Delman et al, 2018; Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%